A memória ancestral de pai Pérsio de Xangô: expansão e consolidação do Candomblé paulista - Eugênio, Rodnei William (2019)
Reconstructing the memory of one of the main leaders of Candomblé de São Paulo means giving voice to a historically discriminated and marginalized group. Our goal is to record life stories in a Terreiro, recovering the memory of its founder. In giving voice to the members of this community, relating their narratives to the sociocultural context, we intend to understand the process of insertion, expansion and consolidation of Candomblé in São Paulo. The considerable conversion of Umbandistas to Candomblé, an almost natural flow between the 1970s and 1980s, lends very peculiar characteristics to this religion in São Paulo and inaugurates the model of what we may call "Candomblé Paulista", a movement with remarkable characters, whose memory can help to understand a fundamental moment in the process of diffusion of Afro-Brazilian religions. The deep relations between the two most popular modalities of Afro-Brazilian religion find in the transit of their followers the foment that dynamizes them. Upon hearing Candomblé's stories of people, particularly those related to the trajectory of Pai Pérsio de Xangô, we sought a dialogue that provided more than the conceptualization of an object. We expanded the field of questioning and reflection to instigate our interlocutors to discover by themselves the truths or concepts about relationships and facts lived, which implied considering the circular movement of memory. Understanding this scenario, in which Candomblé´s Priests and Priestess come from other states to present their services and begin to dispute customers in a religious market, helps to outline the changes that define the Candomblés of São Paulo and what differentiates them from the more traditional ones. Looking at the traditions and worldviews preserved in Candomblé helps us to achieve a more complete conception of what was and still is the reality of the Negro in Brazil and to shape a concept of ancestral memory